Influence of the screens with regular conditions on the immunity and accuracy of subscriber receivers of satellite navigators according to the conditions of radiowaves distribution on the real location - A. S. Abukraa; M. A. Vilkotsky; L. M. Lynkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The estimation of noise immunity of subscriber receivers of satellite navigators (APGSN) under conditions of interference of a coherent, noise-like and FM modulated signal is given. The level of noise immunity in conditions of free space, as well as the real propagation medium between the source of interference and APGSN is estimated. The main studies were carried out by modeling the electromagnetic environment, taking into account the actual position of the subscriber receivers and the source of interference (IP) in the terrain. The analysis of the disturbance zones size was carried out depending on the power of the IP and the propagation medium. The characteristics of interference sources, the geometry of the disturbance zones of APGSN operation at various altitude ratios of APGSN and IP, as well as the location of APGSN relatively to screens of several types are given.